EFFECT OF NEBIVOLOL ON TONE OF TRACHEAL MUSCLE OF GUINEA PIG - Shaukat, Asma; Tariq, Sumbal; Sharif, Mahjabeen; Najmi, Muzammil Hasan (Journal of Ayub Medical College Abbottabad, 2015)
Background: The use of b-blockers is limited by adverse effects such as bronchospasm in asthmatics. Third generation b-blockers such as nebivolol may show better tolerability in asthmatic subjects because they lack b-blocker induced bronchoconstriction. Methods: Effects of nebivolol on the tracheal muscle strips prepared from ovalbumin-sensitised guinea pigs of both sexes were studied. Two sets of experiments were designed after dividing the animals randomly into two groups. Using oxygenated Krebs-Henseleit solution as the nutrient medium, the trachealis muscle activity was measured with isometric force displacement transducer and recorded on 4-channel Oscillograph. Result: Nebivolol 10-6 M did not produce significant effect on contractions evoked by histamine in concentrations ranging from 10-7 M to 10-3 M. The mean of amplitude of contraction for different concentrations of histamine were calculated and compared with the group treated with histamine only. Mean of amplitude of contraction, percent responses and percent deviations when compared with the control group were insignificant (p>0.05). Conclusion: Nebivolol did not affect the tone of airway smooth muscle in ovalbumin-sensitised guinea pigs. Nebivolol may be considered safe in patients with airway disease however, further clinical evaluation and exploratory work is required.